PENGARUH PEMBERIAN PUPUK ORGANIK CAIR LIMBAH IKAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) - Rizky Putra Sampurna; Djarwatiningsih Djarwatiningsih; Guniarti Guniarti (Plumula : Berkala Ilmiah Agroteknologi, 2019)
The purpose of this study was to study the research of liquid organic fertilizer from tilapia waste which can increase the growth and yield of tomato plants (Lycopersicon esculentum mill). This research method was prepared using a completely randomized design (CRD) one factor with 3 replications and in this study all research units were placed randomly. The factor is liquid organic fertilizer with a concentration consisting of 3 levels, with the following details: P1 : 3,5% fertilizer = 35 ml of fertilizer in 1000 ml, P2 : 4% fertilizer = 40 ml of fertilizer in 1000 ml, P3 : 4,5% fertilizer = 45 ml of fertilizer in 1000 ml. Liquid organic fertilizer of fish waste affects the growth and yield of tomato plants caused by several factors, namely: a) Microorganisms : Soil microorganisms have the purpose to increase the efficiency of nutrient uptake by plant roots, b) b) Nutrient uptake mechanism : Nutrients absorbed through the roots and through.